PENGARUH BERMAIN FINGER PAINTING TERHADAP KREATIVITAS ANAK KELOMPOK B DI TK ISLAM HARAPAN INDAH PONTIANAK - Kartini, Kartini; Marmawi, Marmawi; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to determine the effect of creativity between children in group B who were given a finger painting game with those who were not given a finger painting game. The method used is a good experimental method using pretest-postes group design and uses a quantitative approach. The population in this study were 124 and the sample was 38 children divided into control and experimental groups. Data collection techniques used are observation and documentary techniques, while data analysis techniques use an average formula. Based on the results of this study showed that the average of the larger experimental group compared to the average control group. After being given treatment that is 11.26 experimental groups, 6.68 control groups. From the results of the calculation of the t test with the help of the application (SPSS), it is known that the t_count value is 4.066. While the value of ttabel with a significance level of 5% for one side and 0.025 (for two sides) with degrees of freedom (n_1 + n_2-2) = (19 + 19-2) = 36, then obtained 2,028. Because the value of t_count> t table (4.066> 2.028), the null hypothesis (Ho) is rejected. That is, there is the effect of playing finger painting on the creativity of the group B children in the Harapan Indah Islamic Kindergarten in West Pontianak. The influence of 31% is calculated using the formula of coefficient of determination. The conclusion is that there is an effect of playing fingerpainting on children's creativityKeywords: Creativity, Finger Painting